The effect of melatonin supplementation on glycemic control in patients with type 2 diabetes - Lv, Xutong; Sun, Huiqi; Ai, Shuang; Zhang, Dongbin; Lu, Hongxiu (Frontiers in Endocrinology, 2025)
Background and purposeMelatonin supplementation has shown potential benefits in the management of diabetes in clinical trials; however, prior meta-analyses have not specifically focused on individuals with type 2 diabetes mellitus (T2DM). This study investigates the efficacy of melatonin supplementation in improving glycemic control among patients with T2DM by systematically reviewing and analyzing data from randomized controlled trials (RCTs).MethodsA comprehensive literature search was conducted in PubMed, Cochrane Library, Scopus, Web of Science, and Embase from their inception to September 2024. RCTs evaluating the effects of melatonin supplementation in adults diagnosed with T2DM were included. The methodological quality of the studies was assessed using the Cochrane Risk of Bias Tool. Data were synthesized and analyzed using RevMan version 5.3.ResultsA total of nine RCTs were included in the meta-analysis (n=9). These studies collectively involved 427 participants. Melatonin supplementation was associated with a statistically significant reduction in glycated hemoglobin (HbA1c) levels compared to placebo [mean difference [MD]: -0.65; 95% CI: -1.28, -0.02; P = 0.04], However, no significant effect was observed on fasting plasma glucose (FPG) levels [mean difference: -6.40; 95% CI: -15.79, 2.99; P = 0.18].ConclusionThis meta-analysis suggests that melatonin supplementation significantly reduces HbA1c levels in patients with type 2 diabetes mellitus compared to placebo, indicating potential benefits for long-term glycemic control. However, no significant effect was observed on FPG levels.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024629557.